A trajetória da TV UFPB na construção de um veículo de comunicação pública - Vital, Marcos José da Cruz (2020)
The present work aims to tell the story of TV UFPB, a television channel financially supported by the Federal University of Paraíba (UFPB), and suggest initiatives so that such a public communication vehicle can improve the role that is expected from a television fully focused on the public interest, independent and democratic, which aims to offer a programming which is informative, educational, cultural, artistic, scientific, citizen-forming and contemplator of community segments. For these purposes, it was necessary to study historical documents and publications on TV UFPB (ANTUNES DA ROCHA, 2016) and to hear characters who took part in this story or witnessed the related events; to ascertain the characteristics of content production on a public TV (COUTINHO, 2013), as well as other public media outlets (DUARTE, 2009); investigate the history of educational television in Brazil (ANGEIRAS, 2015); examine the legislation relevant to broadcasting and cable broadcasting signals from Brazilian university broadcasters; and research the role of university TV as an instrument for training professionals for the television market (COUTINHO, 2006), sustainable methods of financially supporting public TVs (MAGALHÃES; EVARISTO, 2011), ways to attract a participatory audience (MONTEZ; BECKER, 2005) and ways to promote social media control (MOURA; FEITOSA, 2010). In order for the objective of this investigation to be proven, the following methodologies were adopted for data collection during the exploratory stage: a) bibliographic research, especially of works published by scholarly authors in the field of public communication; b) semi-structured interviews with current professors, former professors and technical-administrative employees of UFPB who could describe facts involving characters and operation of TV UFPB. The results served a chronological report on the first and only university broadcaster in the state of Paraíba with signal transmitted via cable TV and broadcasting; for a more precise definition of what is public communication and what it proposes, especially that exercised by television; so that it is possible to present proposals for improvements aimed at improving TV UFPB, as a vehicle of vocational training, that is sustainable, interactive and open to the participation of society in the definition of its content